1959
DOI: 10.1149/1.2427169
|View full text |Cite
|
Sign up to set email alerts
|

Oxides on the Silver Electrode

Abstract: Silver electrodes were studied by means of potentials and x‐ray diffraction patterns. The silver was charged anodically in 35%KOH by means of either constant current or constant potential, and discharged at a low or high rate. Attempts were made to form an oxide higher than normalAgO by means of anodization. The products of anodization of silver in 2N H2SO4 were determined. The basis for the theory that the oxides of silver are formed by the introduction of oxygen into the octants of the face‐centered cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

1961
1961
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 4 publications
1
48
0
Order By: Relevance
“…8 are not linear (Fig. [2], takes over (13). The ratio is comparatively large initially at the lower charging currents and then it decreases; at high charge currents the ratio increases.…”
Section: Oxidation Of the Electrodesmentioning
confidence: 92%
“…8 are not linear (Fig. [2], takes over (13). The ratio is comparatively large initially at the lower charging currents and then it decreases; at high charge currents the ratio increases.…”
Section: Oxidation Of the Electrodesmentioning
confidence: 92%
“…Some cufi-uaiin in investigations of the silver electrode has beo, cau sed by the report of Jones and Thirsk (6) of what they believed was the x -ray diffracti-n patern of AgO. The pattern reported has since been shown to be that of the so-called silver peroxysulfate Ag 7 OSO 4 and not AgO (7). Bi iggs, Dugdale, and Wynne-Jones (2) confirmed that the final product of anodizing Ag in H 2 SO 4 was mainly the peroxysulfate and not AgO.…”
Section: Application Of This Cell To the Silver Electrode In Koh Solumentioning
confidence: 99%
“…In earlier work at this Laboratory, a silver electrode was removed from a cell-following various amounts of charge or discharge and then examined by x-ray diffraction after rinsing the electrode in water and blotting dry (7). In alkaline electrolyte, the only materials identified were Ag, Ag 2 0, and AgO.…”
Section: Application Of This Cell To the Silver Electrode In Koh Solumentioning
confidence: 99%
“…Much research work was conducted to better understand the charge-discharge behaviour of AgO as an active material for alkaline storage and primary batteries containing silver electrodes [10][11][12][13][14]. Many research works revealed that there are different types of silver oxides and that the behaviour of silver electrode in alkaline electrolyte is fairly complicated.…”
Section: Introductionmentioning
confidence: 99%